UTILIZATION OF THE HEC-RAS METHOD IN ANALYZING INUNDATION AT SUNTER JAYA - Mohammad Immamuddin; Rosyid Al Fiansyah (University Muhammadiyah Jakarta, 2023)
Sunter Jaya channel is one of the channels located in Tanjung Priok District, North Jakarta City which is geographically located at 6 Â° 09'31